What Are the Hemodialysis Patients’ Style in Coping with Stress? A Directed Content Analysis - Mohtasham Ghaffari; Mohammad Ali Morowatisharifabad; Yadollah Mehrabi; Samad Zare; Jafar Askari; Somayeh Alizadeh (International Journal of Community Based Nursing and Midwifery, 2019)
Background: Nowadays, the prevalence of chronic diseases, such as chronic renal failure, is rising. These patients need hemodialysis to continue their treatment, which is a stressful process. This research was conducted with the purpose of explaining coping styles in hemodialysis patients regarding stress factors based on the Lazarus and Folkman’s transactional model. Methods: This qualitative study was conducted as a content analysis. The data collection method was semi-structured interview with 22 patients from dialysis centers in Tehran. The data were collected from October to January 2017. Sampling was purposive and continued until data saturation. Data were analyzed using the directed content analysis method. The process of data analysis proposed by Hsieh and Shannon’s was followed. Results: 106 codes and 24 sub subcategories were obtained through this research and classified into 8 sub-categories of transactional stress model including: problem management, emotional regulation, social support, dispositional coping styles, positive reappraisal, revised goals, spiritual beliefs and positive events; and 3 categories of coping structures that included coping efforts, meaning-based coping and moderators. Conclusion: Dialysis patients are making efforts to cope with their stress in order to reduce their stress; in some cases, these efforts lead to reduction in stress, and in some cases, due to using unsound coping style, they are ineffective or even harmful. Therefore, the necessity of planning and proper interventions is felt by health care providers to control stress in dialysis patients.